Safety and efficiency of porous-tip contact-force catheter for drug-refractory symptomatic paroxysmal atrial fibrillation ablation: results from the SMART SF trial. Issue Volume 20:Issue FI 3(2018) (9th August 2017) - Chinitz, Larry A; Melby, Daniel P; Marchlinski, Francis E; Delaughter, Craig; Fishel, Robert S; Monir, George; Patel, Anshul M; Gibson, Douglas N; Athill, Charles A; Ming Boo, Lee; Stagg, Robert; Natale, Andrea
Abstract: Aims: THERMOCOOL SMARTTOUCH® SF Catheter is a new contact-force (CF)-sensing catheter with 56-hole porous tip designed for improved cooling and reduced fluid delivery compared with a standard 6-hole open-irrigated catheter. The SMART SF study examined the periprocedural safety, acute effectiveness, and procedural efficiency of the catheter for drug-refractory symptomatic paroxysmal atrial fibrillation (PAF) ablation. Methods and results: The prospective, open-label, non-randomized SMART-SF was conducted at 17 US sites. Circumferential pulmonary vein (PV) isolation was performed with confirmation of entrance block in all PVs. Stable ablation sites were identified using CARTO VISITAG™ Module. Primary adverse events (AEs; ≤1 week of index procedure), periprocedural AEs within 30 days of ablation procedure, acute effectiveness (confirmation of entrance block for targeted PVs), CF, and procedural parameters were assessed. Overall, 165 patients were enrolled (mean age, 62.7 years; male, 57.9%; white, 97%; left ventricular ejection fraction, 60.1 ± 7%; left atrium diameter, 38.8 ± 6 mm); 159 underwent radiofrequency ablation and comprised the safety cohort. Primary safety performance criteria were met: primary AE rate was 2.5% (4/159; cardiac tamponade [ n =  2], thrombo-embolism [ n  = 1], transient ischaemic attack [ n  = 1]). All primary AEs resolved/improved within the 1-month follow-up period. Acute procedural effectiveness was attained in 96.2% (95% confidence interval: 92.0–98.6%) of patients. Procedure time, fluoroscopy time, and fluid delivered were observed in comparison to predecessor catheters. Conclusion: In the SMART-SF trial, the predetermined safety performance goal was met, demonstrating the safety and acute effectiveness of the THERMOCOOL SMARTTOUCH ® SF Catheter for PAF ablation.